MOVEMENTS OF ANATOMICAL COMPLEX: CONDYLAR PROCESS, TEMPOROMANDIBULAR JOINT, TEMPORAL BONE - R.S. Palyvoda; A.S. Volovar; A.V. Malikov (Ukrainian Medical Stomatological Academy, 2016)
Based on the fundamental manuscripts and inventions, structure of organs depends on their functions. Each maxillo-facial surgeon should know basics of anatomic relationships of human body, especially maxilla-facial area. Scientists also could prove importance of methods of diagnosis and treatment using anatomy field research based on evidence. One of the objective way to understand structure of organ, investigate changes of tissues, improve your practical skills to make the cadavers dissection. Temporomandibular joint is a well-known double junction complex, but biomechanical features of it had not been enough discussed. Aim of the study is to inquire anatomical particular qualities of human temporomandibular joint for better understanding the fields of stress-strain during biomechanical experiment. Materials and methods. It was used 4 cadavers (department of human anatomy Bogomolets National medical University) for dissection and extraction anatomic complex unilaterally. It was made incision of skin (like preauricular approach) which goes to the angle of mandible and formed muscular-cutaneous flap. Starting from osteotomy ramus of mandible and coronoid process, line goes to the medium cranium fossa (pars petrosal of temporal bone) and behind external auditory meatus. The whole conglomerate of tissues was removed. It consists of condylar process, temporomandibular joint structure and partially of temporal bone. Joint capsule was saved. Protocol of Bioethics Commission was presented and permitted it. We measured the main distances of these region using computer program Simplant (Materialise, Belgium) and data of computer tomography (My Ray Sky View, Hyperion x7, Italy). There were such points and distances: joint space medially, laterally, anterior and posterior, head of condyle, thickness of the bottom of articular fossa, depth of articular fossa and angle of anterior slope. Bone tissue has good quality. Discussion. Comparison of obtained data and information from literature review made differences in 2-4 mm only. According to hardly functional structure of temporomandibular joint, it became possible and permissible. Conclusion. Firstly, we can visually verify that maxillo-facial area is very dangerous, complicated, wellsupplied and innervated region. Our algorithm of taking anatomical complex helped to save structure relations and use it in further scientific work. Such approach development points on obtaining good and confident results. Temporomandibular joint has the "adaptation gap", it helps to make the reserve of mobility of loads in clenching, biting, chewing etc.